What is the effect of the two-child limit on children's school readiness? - Sarah Cattan; Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2025)
Families receiving universal credit usually receive an additional element worth 3,514 per year for each child they have. However, for third and subsequent children born from 6 April 2017 onwards, families do not receive this uplift, due to a policy known as the 'two-child limit'. The policy - intended to align the financial incentives of benefit recipients with families not receiving means-tested benefits with respect to having additional children - has been criticised by its opponents for increasing child poverty, particularly among larger families. While income is strongly correlated with children's educational outcomes, existing evidence on the causal impact of income is more limited and mixed, meaning until now it has been unclear whether, and to what extent, the two-child limit would harm children's educational development. With the first cohort of children affected by the two-child limit now in primary school, this report uses new high-quality administrative data from England to provide the first robust evidence on the two-child limit's impact on school readiness, measured by the early years foundation stage profile (EYFSP) at the end of reception. While this is not the only measure of progress in primary school, it is the benchmark that underpins the government's "milestone" in their "opportunity mission".
Keywords: 330; Education and skills; Employment and income; Poverty; inequality and social mobility; Benefits; Childcare and early years; Early childhood development; Education; Family; Poverty; Schools; Social mobility; Working age benefits